The Distribution of Crisis Credit : Effects on Firm Indebtedness and Aggregate Risk - Huneeus, Federico; Kaboski, Joseph P.; Larrain, Mauricio; Schmukler, Sergio L.; Vera, Mario (Washington, DC: World Bank, 2022)
This paper studies the distribution of credit during crisis times and its impact on firm indebtedness and macroeconomic risk. Whereas policies can help firms in need of financing, they can lead to adverse selection from riskier firms and higher default risk. The paper analyzes a large-scale program of public credit guarantees in Chile during the COVID-19 pandemic using unique transaction-level data on the demand and supply of credit, matched with administrative tax data, for the universe of banks and firms. Credit demand channels loans toward riskier firms, distributing 4.6 percent of gross domestic product and increasing firm leverage. Despite increased lending to riskier firms, macroeconomic risks remain small. Several factors mitigate aggregate risk: the small weight of riskier firms, the exclusion of the riskiest firms, bank screening, contained expected defaults, and the government absorption of tail risk. The empirical findings are confirmed with a model of heterogeneous firms and endogenous default.